Resultado estrutural e impulso fiscal: Uma aplicaç\~aopara as administraç\~oes públicas no Brasil, 1997-2010 - Bernardo Patta Schettini; Raphael Rocha Gouvêa; Rodrigo Octávio Orair (Instituto de Pesquisa Econômica Aplicada (IPEA), 2011)
– This paper estimates the primary structural balance and the fiscal impulse for the Brazilian public administrations from 1997 to 2010. We performed two adjustments: i) initially, one-off measures (including those resulting from creative accounting) were identified; and, ii) after this correction, revenues were adjusted for fluctuations in the level of economic activity and the oil price (in the case of royalties and special participations). The elasticities and the long-run path of the reference series were estimated via the Kalman filter. Our results underscore the relevance of the structural balance in the context of the current debate over credibility and rigidity of fiscal rules, as well as its importance for the monitoring and analysis of the Brazilian fiscal policy stance.
Keywords: E32; E62; H62; 330